Goth : designing darkness - de Rijk, Timo, 1963-; Design Museum Den Bosch; Smulders, Eric, 1966-; Zijlstra, Yvo, 1958- (Den Bosch : Design Museum Den Bosch, 2021)
De mens heeft altijd behoefte gehad aan het geloof in "een dark side", een donkere wereld, bevolkt met geesten, heksen, ... , een universum waarin doden tot leven gewekt worden, vampiers ronddwalen, ... In dit boek maken we kennis met de vele aspecten bij het vormgeven aan dergelijke wereld: de andere kant, de donkere spiegel van onze ziel, geesten, spoken, ... Vooral een fotoboek met stills uit films, foto's, kunstwerken, citaten, ... Heel mooi boek voor wie info zoekt rond het thema "gothic".
The exhibition examines the roots of the Gothic, which reach down into traditional European art history as well as alternative and popular culture. Visitors will discover a rich survey of objects and art from collections including those of the Kröller-Müller Museum, the Musée d'Orsay, the Hamburger Kunsthalle and the Royal Institute of British Architects. The works on display vary from design drawings by Pierre Cuypers and objects by A.W.N. Pugin to furniture by André Lassen and H.R. Giger; prints by Odilon Redon and Félicien Rops to the photographs of Nona Limmen; from nineteenth-century mourning jewellery to the couture of Linda Friesen and Marjolein Turin; and sculptures by Sarah Bernhardt and Emmanuel Frémiet to the contemporary art and design of Sruli Recht, Carolein Smit and Cindy Wright. Exhibition: Design Museum Den Bosch, 's Hertogenbosch, The Netherlands.
This book has been produced to accompany the exhibition
Keywords: Arts, European -- History -- Exhibitions; Goth culture (Subculture) -- Exhibitions